The Role of SGLT2 Inhibitors in Heart Failure: A Systematic Review and Meta-Analysis - Vasiliki Tsampasian; Ranu Baral; Rahul Chattopadhyay; Maciej Debski; Shruti S Joshi; Johannes Reinhold; Marc R Dweck; Pankaj Garg; Vassilios S Vassiliou (Cardiology Research and Practice)
Aims. Recent randomised controlled trials (RCTs) have shown a significant prognostic benefit of sodium-glucose cotransporter 2 (SGLT2) inhibitors in the cardiovascular (CV) profile of patients with diabetes. This systematic review and meta-analysis aim to provide a concise evaluation of all the available evidence for the use of these agents in patients with heart failure (HF) regardless of their baseline diabetes status. Methods and Results. PubMed, Web of Science, and Cochrane library databases were systematically searched from inception until November 20th 2020. Eight studies consisting of 13,275 patients were included in the meta-analysis. For the total population, SGLT2 inhibitors reduced the risk of all-cause mortality (HR: 0.83; 95% CI: 0.75–0.91; I2 0%), hospitalisation for HF (HR: 0.68; 95% CI: 0.61–0.75; I2: 0%), CV death (HR: 0.82; 95% CI: 0.74–0.92; I2: 0%), and hospitalisation for HF or CV death (HR: 0.72; 95% CI: 0.66–0.78; I2: 0%). Subgroup analyses of the total population according to the diabetes status showed that SGLT2 inhibitors significantly reduced the risk of hospitalisation for HF (HR: 0.68; 95% CI: 0.61, 0.75; I2: 0%), as well as the risk of hospitalisation for HF or CV death (HR: 0.72; 95% CI: 0.66, 078; I2: 0%) and CV death (HR: 0.82; 95% CI: 0.74, 0.91; I2: 0%). Conclusions. The results of this meta-analysis confirm the growing evidence in the literature of the favourable profile of SGLT2 inhibitors in cardiovascular outcomes and mortality in patients with heart failure regardless of the baseline diabetes status. This systematic review has been registered with PROSPERO (CRD42021224777).